The Pengaruh Metode Talaqqi terhadap Peningkatan Hafalan Al-Qur'an dalam Pembelajaran Tahfidz : Metode Taqqi - Siti Nurmayantu, Risa (MUNTAZAM, 2024)
The research aims to determine the increase in students' memorization of the Qur'an through the application of the talaqqi method to class II students at Al-Maruf Elementary School for the 2022-2023 academic year. This research is a quantitative experimental research with a one pretest-posttest design involving a sample of 21 students. The data collection technique was carried out by memorizing the Al-Qur'an. Meanwhile, quantitative analysis uses the normality test, homogeneity test, gain normalization test and average difference test using SPSS software assistance. The talaqqi method affects the memorization of the Al-Qur'an for second grade students at Al-Maruf Elementary School. The result of tcount = 6.304 > ttable = 2.079, with a sig. 0.00 < α of 0.05 then H0 is rejected and Ha is accepted, which means there is an average difference between the pretest and posttest ability to memorize the Qur'an. The N-Gain is (0.594) with a moderate increase, indicating that the effect of the talaqqi method on the ability to memorize the Qur'an is 59.4%, while the other 40.6% is influenced by other factors outside of this study.